1990
DOI: 10.1073/pnas.87.5.1884
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal reorganizations responsible for the phorbol ester-induced formation of cytoplasmic processes: possible involvement of intermediate filaments.

Abstract: The tumor promoter phorbol 12-myristate 13-acetate (PMA) induces characteristic reversible changes of cell shape in certain fibroblastic lines: motile lamellas are transformed into noncontractile narrow processes; simultaneously, the actin microframent network of lamellas is locally disorganized. This reaction to PMA may be regarded as a prototype of reorganizations involving formation of stable cytoplasmic processes. Specific drugs, Taxol and Colcemid, were used to study the role of microtubules and vimentinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…What is the nature of these possible interactions? The presence of microtubules is not essential for disorganization of actin accompanying lamella-to-stalk transformation: these transformations can be induced by PMA in the cells with microtubules depolymerized by Colcemid (31). Intermediate filaments are the only type of cytoskeletal element that is always found in cytoplasmic stalklike processes induced by PMA in all types of experiments; as already indicated, intermediate filaments are usually absent from lamellas before their transformation into these processes.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…What is the nature of these possible interactions? The presence of microtubules is not essential for disorganization of actin accompanying lamella-to-stalk transformation: these transformations can be induced by PMA in the cells with microtubules depolymerized by Colcemid (31). Intermediate filaments are the only type of cytoskeletal element that is always found in cytoplasmic stalklike processes induced by PMA in all types of experiments; as already indicated, intermediate filaments are usually absent from lamellas before their transformation into these processes.…”
Section: Resultsmentioning
confidence: 81%
“…Besides microtubule modification, lamella-to-stalk transformation also involves the profound reorganization of another cytoskeletal system, actin microfilaments; the network of microfilaments present in the lamellas is dismantled and actin cortex loses its contractility (3,4,30,31).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, fibroblast studies showed that microtubules and actin filaments mutually influence each other. For example, increased microtubule growth in fibroblasts after the washout of the microtubule-depolymerizing drugs nocodazole or colcemid increases actin polymerization and dynamics of lamellipodia (Bershadsky et al, 1990;WatermanStorer et al, 1999) by activating the Rho GTPase Rac1 (Waterman-Storer et al, 1999). Consistent with such interpretation, we found that modest nocodazole concentrations caused neurons with splayed microtubules at the tips, enlarged growth cones, and impaired growth cone dynamics and axon growth, recapitulating the phenotype of DN-CLIP-expressing neurons (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore interesting to investigate whether this disruption also would inhibit stimulation-induced ruffling and lamellipodium formation. Because PMA has been shown to induce the reorganization of the actin cytoskeleton Bershadsky et al, 1990;Downey et al, 1992), we used this agent to study ruffle and lamellipodium formation in the presence or absence of microtubules. Upon PMA treatment of GFP-actin-transfected cells, it was possible to induce extensive ruffling and lamellipodium formation ( Figure 3A).…”
Section: Pma-induced Ruffling Is Rac-dependentmentioning
confidence: 99%